Takhrij and Syarah Hadith of Chemistry: Benefits of Talbinah in Preventing Depression - Silvianaqori Nurulaeni; Salsabilla Desviani Putri; Nisa Nur Khasanah; Siti Chodijah; Yumna Yumna (UIN Sunan Gunung Djati Bandung, 2021)
This research aims to discuss the hadith of the Prophet Mumahammad SAW. about talbinah. This research method is qualitative through the takhrij and syarah hadith approaches with chemical analysis. The results and discussion of this study is that talbinah is useful for preventing depression because it contains vitamin B12, vitamin D, and magnesium. Depression is a mood disorder characterized by feelings of deep sadness and a sense of indifference. The conclusion of this research is takhrij and syarah hadith of the Prophet Muhammad SAW. about talbinah by chemical analysis has benefits in reducing and preventing depression.